Brand authenticity: conceptualization and future directions - Rosado-Pinto, F.; Loureiro, S. M. C. (The Sage handbook of brand management, 2026)
Authenticity plays a critical role in contemporary society (Lehman et al., 2019). In the last 20 years, academic research about the topic has grown significantly both in marketing and in related fields (Campagna et al., 2023; Nunes et al., 2021), as people value authentic products, services and experiences (Fritz et al., 2017). The study of authenticity has been common to different fields of research, namely, management, anthropology, philosophy, sociology, psychology or marketing (Bruhn et al., 2012; Fritz et al., 2017; Kovács, 2019; Lehman et al., 2019; Nunes et al., 2021). According to Fritz et al. (2017), in philosophy, authenticity is linked to moral behavior and, within sociology, the concept is mainly perceived as a social construction. In anthropology, authenticity is related with the preservation of beliefs, values and cultural norms and in psychology “authenticity is rooted in subjective internal experiences that have implications for one´s self-knowledge, understanding and relationship behavior” (Fritz et al., 2017, p. 326).